FREQUENCY AND RISK FACTORS OF BREAST CANCER AMONG YOUNG AND MIDDLE-AGED WOMEN.: JPUMHS;2024:14:04,226-233. http://doi.org/10.46536/jpumhs/2024/14.04.582 - Sehrish Rasooll, Nousheen Khaleeq2, Amna Begum3, Fatul4, Waseem Akram5, Kalsoom Kalhoro6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Breast cancer is the leading cause of cancer related deaths worldwide and becoming more common in Pakistan. Trend is now shifting to young and middle-aged women. Data is limited in this regard from Pakistan. That is why this study aims to determine the prevalence and risk factors of breast cancer among young and middle-aged women. METHODS: A prospective observational study was conducted in the department of Gynecology & Pathology for a period of 8 months from March 2024 to October 2024 at Peoples University of Medical and Health Science for women, Shaheed Benazirabad. All the suspected women of young age 18 to 35 years and middle age ≥36 to 55 years groups were included for breast cancer frequency and associated risk factors. RESULTS: A total of 213 patients were included for final analysis. Significant proportion of patients with age more than 35 years middle age were diagnosed with carcinoma of breast. Patients who had late marriage 30.43±7.02 years, patients belong to middle socioeconomic background n = 164, 76.99%, patients with no children n = 8, 3.75%, patients with positive family history of breast cancer n = 32, 15.02%, and patients who had early menstruation were more likely to have breast cancer, p value <0.05. CONCLUSION: Breast cancer is common among middle aged women but young women also show an increase in its frequency. Late marriages, early menstruation, and positive family history of breast cancer are the leading causes of carcinoma of breast observed in our study